2023
DOI: 10.1007/s00705-023-05703-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of coronaviruses in bats and rodents in northern and central Argentina

Abstract: Due to the present pandemic situation and the many animal species that are epidemiologically involved, there has been a surge of renewed interest in investigating the coronavirus (CoV) population circulating in wildlife, especially bats and rodents, which are potential reservoirs of new human pathogens. In Argentina, information about the viruses present in these mammals is very limited. To investigate the presence of coronaviruses in this country, we obtained 457 samples from hematophagous, insectivorous, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…To date, coronavirus studies carried out on bats from Argentina have corresponded to surveillance campaigns based on the detection and sequencing of a conserved RdRp region ( 27 , 28 ). This strategy has been useful in exploring the presence, diversity, and phylogenetic relationships of coronaviruses circulating in some species of bats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, coronavirus studies carried out on bats from Argentina have corresponded to surveillance campaigns based on the detection and sequencing of a conserved RdRp region ( 27 , 28 ). This strategy has been useful in exploring the presence, diversity, and phylogenetic relationships of coronaviruses circulating in some species of bats.…”
Section: Discussionmentioning
confidence: 99%
“…The novel genomes and protein-encoding genes (Spike and RdRp) were aligned with selected context sequences of representative species belonging to the family Coronaviridae (see Table S2 for accession numbers) using MAFFT v7.453 ( 26 ) and ClustalW algorithm v2.1. The RdRp gene data set was constructed with AlphaCoV partial sequences from Argentina ( n = 38) ( 27 , 28 ), the U.S. ( n = 143), and other countries ( n = 21). Sequences from Beta-, Gamma-, and DeltaCoV genera were included as outgroups ( n = 37).…”
Section: Methodsmentioning
confidence: 99%
“…Another study on nine different frugivorous and insectivorous species in Costa Rica, Panama, Ecuador, and Brazil revealed that alpha and betaCoV RNA were detected in 50 of more than 1500 bats, indicating the wide distribution between different bat species [112]. In Argentina, alphacoronaviruses were detected by PCR in oral and fecal samples collected from hematophagous, insectivorous, and frugivorous bats [113].…”
Section: Central and South Americamentioning
confidence: 99%